Development of Problem Based Learning (PBL) Electronic Student Worksheets (E-LKPD) to Improve Students' Mathematical Problem Solving Ability - Rani Gebyta Sinuraya; Suci Frisnoiry (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to determine the validity, practicality, and effectiveness of the developed Problem Based Learning (PBL) Electronic Student Worksheets (E-LKPD) which will be used to improve students' problem solving abilities on the material system of three variable linear equations in class. X-2 Budi Murni 2 Catholic Private High School Medan. This research is a type of research and development (Reserch and Development) using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results of the research show that the developed electronic LKPD is valid. This can be seen from the results of the assessment given by the validators with a validity score of 3.62 in the "valid" category. The practicality of the LKPD by the teacher was 3.82 and the readability test score by students was 3.78 in the "Very Practical" category. The effectiveness of electronic LKPD can be seen from the students' classical learning completeness which reached 85.71%, the average students' mathematical problem solving abilities increased by 34.86% and through the N-Gain test showed students' problem solving abilities increased by 0.721 and student response questionnaire obtained a percentage of 82%.